Aerobic oxidation of the C–H bond under ambient conditions using highly dispersed Co over highly porous N-doped carbon. Issue 6 (20th February 2019) - Nie, Renfeng; Chen, Jingwen; Chen, Minda; Qi, Zhiyuan; Goh, Tian-Wei; Ma, Tao; Zhou, Lin; Pei, Yuchen; Huang, Wenyu
Abstract : Highly dispersed Co in porous N-doped carbon is active for oxidation of the C–H bond to ketones under 60 °C and 1 atm O2, which is 41.3 times more active in comparison to ZIF-67-derived Co catalyst. Abstract : Highly dispersed Co sites in highly porous N-doped carbon (Co-NC) were synthesized by high-temperature pyrolysis of Zn/Co bimetallic zeolitic imidazolate framework-8 (Co x Zn100− x -ZIF). Wide characterization indicated that the pyrolysis atmosphere and temperature play crucial roles in the metal dispersion and pore structure of the resulting materials. A hydrogen treatment at elevated temperatures is found to favour the Zn volatilization and restrict the pore shrinkage of the ZIF precursor, thus yielding efficient catalysts with highly dispersed Co, a high surface area (1090 m 2 g −1 ) and pore volume (0.89 cm 3 g −1 ). When used as a catalyst for aerobic oxidation of ethylbenzene (EB), Co1 Zn99 -ZIF-800-H2 contributes to 98.9% EB conversion and 93.1% ketone selectivity under mild conditions (60 °C, 1 atm O2 ), which is 41.3 times more active in comparison to the ZIF-67-derived Co catalyst. Co-NC is stable and could be reused four times without obvious deactivation. This catalyst displays good chemoselectivity to the corresponding ketones when using a broad scope of hydrocarbon compounds.